A COMPARATIVE STUDY ON THE EFFECT OF PARAFFIN WAX THERAPY WITH MANUAL MOBILIZATION VERSUS ULTRASOUND THERAPY WITH MANUAL MOBILIZATION ON PAIN, RANGE OF MOTION AND FUNCTIONAL STATUS OF SHOULDER IN DIABETIC SUBJECTS WITH ADHESIVE CAPSULITIS - Viswanath Reddy, A.; Raghava Krishna, S.; Madhavi, K.; Sachan, Alok (International journal of physiotherapy, 2019)
Background: The shoulder is a complex joint that plays a crucial role in many activities of daily living. Adhesive capsulitis is defined as a painful and disabling condition in which the capsule and the connective tissue surrounding the glenohumeral (GH) joint becomes inflamed, leading to restriction of range of motion in the joint. A wide range of physical therapy interventions are used to improve the joint range of motion in subjects with adhesive capsulitis. Earlier, isolated studies were done on the effectiveness of paraffin wax therapy and ultrasound therapy in subjects with adhesive capsulitis. The need of the present study was to compare the effect of paraffin wax therapy with manual mobilization and ultrasound therapy with manual mobilization on pain, shoulder ROM and functional status in diabetic subjects with adhesive capsulitis. Methods: Subjects for the study were recruited from the outpatient department of endocrinology and physiotherapy. The size of the sample is 80 (eighty subjects) 40 in each group, and study design is an experimental study design (Non-randomized open-label study). The pretreatment values of pain and functional status of the shoulder were assessed using Shoulder Pain and Disability Index (SPADI) scale and ROM was assessed using a universal goniometer. The subjects in the paraffin wax therapy group received wax therapy for 10 minutes and undergone manual mobilization. The subjects in the ultrasound therapy group received ultrasound therapy (3MHz) for 10 minutes and undergone manual mobilization. The treatment was given for 3 sessions per week for 6 weeks and post-treatment values were noted for the subjects of both the groups. Results: There was an improvement of ROM of external rotation, pain & functional status of the shoulder in subjects who underwent paraffin wax therapy with mobilization and ultrasound therapy with mobilization. When comparing both the groups, the subjects who underwent paraffin wax therapy with mobilization have better outcomes than ultrasound therapy with the mobilization group (p< 0.05). Conclusion: There was an improvement of ROM of external rotation, pain & functional status of the shoulder in subjects who underwent paraffin wax therapy with mobilization and ultrasound therapy with mobilization. When comparing both the groups, the subjects who underwent paraffin wax therapy with mobilization have better outcomes than ultrasound therapy with the mobilization group.